2021
DOI: 10.4236/jwarp.2021.135020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distance of Sanitary Pits on the Microbial and Heavy Metal Levels in Hand Dug Well Water Samples Consumed by People Living in Akwuke, Enugu South Local Government Area of Enugu State

Abstract: Studies were carried out to assess the effect of distance of sanitary pits on the microbial and heavy metal levels in hand dug well water samples consumed by people living in Akwuke, Enugu South Local government area of Enugu State, using standard biochemical and spectrophotometric analysis. The well water samples were digested with aqua-regia and four heavy metals (Pb, Cd, Cu and Zn) were assayed in the well water samples at sampling distances of 3, 6 and 10 m respectively from the sanitary pits. The range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The toxic effects of Pb to humans and animals even at low concentrations are well documented (Okeke et al, 2016;Aniobi et al, 2021;Gupta et al, 2021).…”
Section: Domestic Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…The toxic effects of Pb to humans and animals even at low concentrations are well documented (Okeke et al, 2016;Aniobi et al, 2021;Gupta et al, 2021).…”
Section: Domestic Animalsmentioning
confidence: 99%
“…Bhat et al, (2010) observed that many farmers' non-profiling and less consciousness on the food and feedstock consumed especially by non -ranched domestic animals could be the main reason for the increased level of toxic metals as well as decreased level of trace elements that these animals are exposed to. Although copper is a trace element required by animals and humans for optimum enzyme and biochemical function, at excess levels can exert toxicities to vital organs such as the liver and kidney (Okeke et al, 2016;Aniobi et al, 2019;Okeke et al, 2021).…”
Section: Domestic Animalsmentioning
confidence: 99%
See 3 more Smart Citations